Salmonella Typhi gut invasion drives hypoxic immune subsets associated with disease outcomes - Noa Bossel Ben-Moshe; Shelly Hen-Avivi; Liron Levy Efrati; Leia Veinman; Jennifer Hill; Daniel O’Connor; Marije Verheul; Lisa Stockdale; Florence McLean; Andrew J. Pollard; Roi Avraham (Nature Communications)
Abstract Salmonella Typhi (S. Typhi), the causative agent of typhoid disease, remains a major public health concern. Owing to the human-restricted nature of S. Typhi, studies of typhoid pathogenesis in animal models are limited to a murine non-typhoidal pathogen. More recently, human challenge models have been conducted, providing insight into immune correlates of infection outcomes, which are still incompletely understood. Here, we performed an integrated single-cell analysis of immune responses from the human S. Typhi challenge model and mouse model of typhoid disease, to associate biological mechanism with human infection outcome. Most prominent, we revealed immune subsets with a hypoxia-related signature in the blood of individuals who developed disease in the human challenge model. This signature was also evident in the mouse model in activated macrophages infiltrating into the Peyer’s patches, but not during infection with a mutant strain impaired for gut invasion. We further identified hypoxia-related signature as a general immune correlate of disease outcome in other infection-and inflammatory-related diseases. Collectively, we identified a hypoxia-associated immune signature that correlates with disease outcomes in humans. Using a mouse model, we demonstrated that this signature is driven by bacterial invasion to the Peyer’s patches, implicating a causal role in the pathogenesis of typhoid fever.